Formação continuada de diretores: uma análise das significações atribuídas por diretoras de centros de educação infantil da rede parceira sobre seu papel profissional - Amaral, Roberta Souza do (2022)
This qualitative research aims to analyse and understand what it means to be a school principal for professionals working at kindergarten centers that belong to the Partner Education System. Specific objectives are: (1) to apprehend mediations that constitute such meanings; (2) to identify deployments of such meanings in action proposals happening in their workplace; and (3) to investigate training necessities of this group of principals. The participants are eight principals, working at institutions under the administration of a Civil Society Organization which is partnered with the City Hall in São Paulo. To analyse the objectives, we considered that the pandemic caused by the new coronavirus brought several changes for the workers of education, so its coming to Brazil in March 2020 is our time cut. We chose Sociohistorical Psychology as our theoretical-methodological reference. As source of data, we requested that the principals wrote individual narratives. To complement our analysis, we used narratives about the processes developed during training sessions, written by the trainer. Procedures of analysis used the meaning core, which allowed us to approach the processes of building the meanings attributed by the principals, making sure analysis would go beyond the apparent, showing mediations of what constitutes being a principal. Analysis of the meanings expressed by the group of principals resulted in an indication that the changes triggered by the historical context of the new coronavirus pandemic had a negative impact on the management of Kindergarten Centers, given it brought about the necessity of reorganizing work. On the other hand, it contributed with training processes since it triggered the necessity to develop and learn to adequate to the new demands and to working from home. Final considerations indicate topics that contribute with the planning of training for principals, in order to make it more significant and closer to their daily challenges